2021
DOI: 10.3390/ani11041104
|View full text |Cite
|
Sign up to set email alerts
|

PK/PD Analysis of Marbofloxacin by Monte Carlo Simulation against Mycoplasmaagalactiae in Plasma and Milk of Lactating Goats after IV, SC and SC-Long Acting Formulations Administration

Abstract: Contagious agalactia is a mycoplasmosis affecting small ruminants that have become an important issue in many countries. However, PK/PD studies of antibiotics to treat this problem in lactating goats affected by Mycoplasma (M.) agalactiae, the main CA-causing mycoplasma are almost non-existent. The aims of this study were to evaluate the plasma and milk disposition of marbofloxacin in lactating goats after intravenous (IV), subcutaneous (SC) and subcutaneous poloxamer P407 formulations with and without carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Statistical comparison of fAUC 24 / MIC ratios obtained with both models for each growth medium and inoculum tested show significant differences. These findings suggest the PK/PD cutoff points determined are highly dependent on the growth medium and bacterial density [ 15 , 23 ]. The highest values have always been obtained in serum and milk, which are more representative biological fluids than artificial media [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Statistical comparison of fAUC 24 / MIC ratios obtained with both models for each growth medium and inoculum tested show significant differences. These findings suggest the PK/PD cutoff points determined are highly dependent on the growth medium and bacterial density [ 15 , 23 ]. The highest values have always been obtained in serum and milk, which are more representative biological fluids than artificial media [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For low and high inoculum, median values close to 50–120, 80–160 and 100–175 were obtained in CAMHB, serum, and milk, respectively, and fall in the range of standardized values for fluoroquinolones of 50–125 that have been widely described [ 9 ]. However, it is necessary to indicate that the numerical values recommended to establish the PK/PD cutoff points for concentration-dependent antimicrobial drugs as fluoroquinolones have been generated in experimental infections in laboratory animals or in human clinical trials [ 23 , 44 ]; thus, these observed ratios might not be applicable to goat infections or to other infections in ruminants [ 45 , 46 , 47 , 48 , 49 ]. In the same way, fAUC / MIC ratios for ruminant species have been described in different experiments with TKC with values lower than 100 or higher than 180, especially with high bacterial densities [ 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations